The acquisition of psychomotor skills through scientific instrumentation andragogical approach in learning style - Ratim, Suzana; Zakaria, Rosnah; Md. Akhir, Rabiatuladawiyah; Ibrahim, Norazura; Husin, Maryam (Penerbit UiTM (UiTM Press), 2026)
This study investigated the impact of the Scientific Instrumentation Andragogical Approach (SIAA) on the development of tertiary students’ psychomotor skills, using experiential and self-directed laboratory learning. A total of 135 Applied Sciences students at Universiti Teknologi MARA, Shah Alam completed validated questionnaires. Reliability analysis yielded excellent internal consistency of the Practical Skill Acquisition (0.938), Student-Centered Learning (0.932), and Skill Application & Future Preparedness (0.898). Correlations between 0.694 – 0.749 demonstrated strong construct coherence. Although data significantly departed from perfect normality, skewness and kurtosis that were within ± 2 validated reasonable interpretation. Results substantiated high self-efficacy and readiness for real- world application. Compared to the other dimensions, skill applicability had the strongest influence. The SIAA effectively boosted students’ psychomotor competence, autonomy, and reflectiveness of the learning style. In application, the approach is consistent with adult learning andragogy and aligns the laboratory practice with employability-focused higher-education outcomes.